2016
DOI: 10.1002/rcs.1730
|View full text |Cite
|
Sign up to set email alerts
|

Early operative outcomes and learning curve of robotic assisted giant paraesophageal hernia repair

Abstract: BACKGROUND We have previously described our technique of Robotic-Assisted Giant Paraesophageal Hernia Repair (RA-GPEHR). The purpose of this study was to report our initial experience, early outcomes and learning curve with RA-GPEHR using a four-arm robotic platform. METHODS 24 consecutive patients presenting with symptomatic giant paraesophageal hernias (GPEH) underwent RA-GPEHR from April 2011 to February 2014. Peri-operative data and short-term patient outcomes were assessed by retrospective review of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…It would undoubtedly be useful to be able to determine the effect of subtype of paraesophageal hernias on outcomes to better identify a subgroup for which robotic assistance is useful. 7 Some of the need for postoperative endoscopy and revisional operations might stem from having recurrent diaphragmatic hernia in our analysis. Repairs of recurrent hernia would be expected to be associated with increased risk of repeat postoperative interventions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It would undoubtedly be useful to be able to determine the effect of subtype of paraesophageal hernias on outcomes to better identify a subgroup for which robotic assistance is useful. 7 Some of the need for postoperative endoscopy and revisional operations might stem from having recurrent diaphragmatic hernia in our analysis. Repairs of recurrent hernia would be expected to be associated with increased risk of repeat postoperative interventions.…”
Section: Discussionmentioning
confidence: 94%
“…be that the minimally invasive approaches are associated with increased risk of stricture at the site of the repair, or the increased use of endoscopy might be driven by the fact that the providers performing the minimally invasive approaches to repair are more facile with endoscopy and are routinely performing follow-up endoscopy in their patients. 7,9 The dataset does not provide enough detail about reasons for post-index readmission and intervention to allow for a determination of cause for this disparity. Overall, the rate of post-index hospitalization encounters and rate of endoscopy were relatively low across cohorts with no marked difference in rates between cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Similarly, studies of robotic hiatal hernia and fundoplication have found it to be safe with equivalent outcomes to laparoscopy, with no clear improvement in outcomes over the traditional laparoscopic approach. 13,14 Recently however, Solomon et al performed a large review of the Society of Thoracic Surgery database between 2012 and 2017. All repairs were performed at the same institution and it is by far the largest series of its kind, with n = 151 in the laparoscopic arm and n = 142 in the robotic arm.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic repair is technically difficult in this subset of patients because of the presence of great anatomical distortion, which requires meticulous dissection of the hernia sac that must be accomplished with limited motion of rigid instruments and poor ergonomics [20][21][22]. Furthermore, various reports published in the literature (Table 1) suggest that there is a higher recurrence rate after the laparoscopic approach for giant hiatal hernia (GHH) repair than after conventional surgery [28][29][30]. Andujar et al (2004) [15] analyzed a total of 166 patients with a mean age of 68 years who underwent the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%